Performing feminism : the evolution of the female in the legend of Robin Hood - Ess, Aubrey Gabrelyn (2014)
Since the formulation of its earliest fourteenth-century ballads through twenty-first century films, the legend of Robin Hood presents an evolution of feminism even before the first, second and third waves of feminism. Though it portrays a patriarchal representation of females, the performances in its tales also resist this prescribed behaviour. For it is the legend’s performance tradition that creates its precocious and prevalent examples of feminism, whether through the oral tradition of ballads, the dramatic performance of plays or films, or linguistic performances like speech acts in novels. The legend’s feminism indicates how both involuntary and voluntary performance can change one’s gender and undermine patriarchal representations of gender. Tales contain only temporary moments of feminism, as females ultimately submit to patriarchy for reasons like romantic love. Despite its ultimately conservative gender politics, however, the legend’s underlying feminism demonstrates the performance tradition’s ability to craft progressive ideas before their time, or engage with multiple ideas reflective of their time. Consequently, the performance of feminism reveals a complexity to popular legends like Robin Hood, deserving of greater attention in gender or theatrical studies.